Frontiers in Advanced Control Systems - Luiz de Oliveira Serra, Ginalber; Luiz de Oliveira Serra, Ginalber (IntechOpen, 2012)
This book pretends to bring the state-of-art research results on advanced control from both the theoretical and practical perspectives. The fundamental and advanced research results as well as the contributions in terms of the technical evolution of control theory are of particular interest. This book can serve as a bridge between people who are working on the theoretical and practical research on control theory, and facilitate the proposal of development of new control techniques and its applications. In addition, this book presents educational importance to help students and researchers to know the frontiers of the control technology.
English
Keywords: Automatic control engineering; Automatic control engineering